A practical study of the problems of queues for vehicles in some filling stations in the city of Baghdad - رضا, صباح منفي; ابراهيم, سماهر طارق (Journal of Economics and Administrative Sciences, 2011)
According to the circumstances experienced by our country which led to Occurrence of many crises that are the most important crisis is gaining fuel therefore , the theory of queue ( waiting line ) had been used to solve this crisis and as the relevance of this issue indirect and essential role in daily life  .This research aims to conduct a study of the distribution of gasoline station in (both sides AL – kharkh and AL Rusafa, for the purpose of reducing wasting time and services time through the criteria of the theory of queues and work to improve the efficiency of these stations by the other hand. we are working to reduce the cost of station and increase profits by reducing the active service unit so that do sent affect the process of waiting and the time of performance services.   the possibility of applying more than statistical distribution of data acess rate and the rate of services and best selection of distribution which reducing the time of service through statistical techniques to demonstrate the behavior of the data (access rate and service rate) with in the statistical distribution that are consistent with the nature of data and select the best statistical distribution which affects the theory of the queues during the time of service and waiting time there are three categories for better know ledge of distribution are  • Poisson with Exponential• Poisson with Weibull • Erlang with Exponential Asset of on clusion had been emerged from the study as using such (G /G /C) queue model which includes the use through the current reality stations like AL– idrisi, AL– Mustansiriya and AL– galani the waiting time for the customer of services is mostly doesn’t have time to wait therefore, we suggest reducing the number of units in station and increase profit through the groups note that the distribution stations animate the few number of unit operating station such as AL– karkh (AL- khadra, AL– yarmouk and AL– shorta al– ola) the data access and service distributed according to the distribution of Poisson with Weibull the data access Service and distributed according to Poisson With Weibull station do the large number of units operating station such as AL– Rusafa  (AL– idrisi, AL– Mustansiriya and AL– galani ) the data access and service distribution according to the distribution of Poisson with Exponential and Poisson with Weibull   .